STUDENTS' OPINIONS ABOUT SCIENCE AND TECHNOLOGY IN TURKEY AND THE UNITED STATES: A CROSS-CULTURAL STUDY - Hünkar Korkmaz; Julie Anne Thomas; Nilgun Tatar; Serpil Aktas Altunay (Informascope, 2017)
The aim of this study is to determine the thoughts of Turkish and American middle school students on science and technology. One intact school was assigned randomly for this study from both countries. The sampling of the study contains 479 students (363 Turkish students, 116 American students) from two countries aged between 11 and 13. The data for the study were obtained by using ROSE Survey. The results of the study revealed similarities and dissimilarities on science and technology between the students of the two countries. The findings of the study are thought to improve the education of universal science and technology and to contribute to the researchers doing research on comparative education and cultural diversity and to the literature of international science education. Keywords: curriculum and instruction, science education, middle school